Customer Satisfaction Mapping of Hot Mix Asphalt Products Using Importance-Performance Analysis - Herlina Mantolas; V. Reza Bayu Kurniawan; Syamsul Ma'arif; Dương Quế-Nhu (Universitas Sarjanawiyata Tamansiswa, 2025)
The construction industry, particularly road construction, supports economic growth and enhances community mobility. One of the primary challenges is ensuring that the quality of hot mix asphalt (HMA), a critical component in road construction, aligns with customer needs and expectations. This study aims to evaluate customer satisfaction with HMA products produced by PT. SKS in Yogyakarta. The Importance-Performance Analysis (IPA) approach was employed to identify gaps between the product's actual performance and the importance level expected by customers. Data were collected from 25 respondents using a Likert-scale questionnaire covering 20 service attributes, including guest facilities, product services, and quality control. The data were analyzed using a Cartesian diagram to map attributes into four priority quadrants. The findings revealed that the average performance score (3.93) was slightly lower than the average importance score (4.13), indicating gaps in several attributes. Attributes such as the availability of project safety shoes (Q8) and accessibility (Q9) fell into Quadrant A, requiring immediate improvement. Meanwhile, attributes like product quality (Q14) and delivery reliability (Q12) in Quadrant B must be maintained. This study concludes that enhancing the priority attributes in Quadrant A can significantly improve customer satisfaction. The findings provide strategic recommendations for the company to enhance efficiency, improve product quality, and meet customer expectations.